2015
DOI: 10.1016/j.pmrj.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Age‐Related Decline in the Performance of the Transverse Abdominis Muscle

Abstract: The core abdominal muscles provide support to the low back. One of the principle muscles of this group is the Transverse Abdominis (TrA) but being a deep muscle it is difficult to measure without invasive procedures. As we age skeletal muscle performance declines. The ageing population also suffers from low back pain and it is hypothesised that a decline in core muscle performance may contribute. Some previous investigations have used intramuscular EMG to assess TrA performance but no study has previously look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…However, our results also show that young adults had significantly greater relative average TrA thickness than the middle-aged group in all exercises. This finding is consistent with previous research [ 6 , 30 , 31 ] as well as with a systematic review that has shown that younger individuals can recruit TrA higher than older individuals [ 40 ]. Our findings may be explained by several factors, such as differences in neuromuscular control, muscle fiber type composition, or hormonal status between younger and older individuals [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results also show that young adults had significantly greater relative average TrA thickness than the middle-aged group in all exercises. This finding is consistent with previous research [ 6 , 30 , 31 ] as well as with a systematic review that has shown that younger individuals can recruit TrA higher than older individuals [ 40 ]. Our findings may be explained by several factors, such as differences in neuromuscular control, muscle fiber type composition, or hormonal status between younger and older individuals [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported conflicting results on which exercises elicit higher TrA recruitment, such as upper or lower limb lifts from the quadruped position [ 25 ], prone plank [ 26 ], bridge exercises with abdominal bracing [ 27 , 28 ], or planks with opposite arm–leg elevation [ 29 ]. Moreover, some studies have suggested that there may be age-related differences in TrA activation [ 30 , 31 ]. A study by Kellis et al [ 6 ] showed that young adults had the greatest relative transversus abdominis thickness during contraction compared to middle-aged adults, adolescents, and children.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that muscle stiffness is significantly higher in younger versus older adults (Do et al, 2021). Gaudreault et al (2021) reported that TrA activation and thickness decreased with age, whereas connective tissue (epimysium fascia) increased, and Davies et al (2016) reported that TrA recruitment in older adults was significantly slower than that in younger adults. Core muscle deterioration also occurs with aging and may contribute to decreased TrA stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the mechanism of muscle stabilization, studies evidence that -when there is reduction of muscle fibers and reduction in the cross-sectional area of the stabilization muscles and consequent inability to support the demand imposedother muscles tend to compensate its function. These compensations would cause a postural imbalance with nonphysiological biomechanical responses that would trigger a painful process [14][15][16][17] . This would justify the results found in our study, which showed that the OWRS had higher pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of muscle fibers resulting from sarcopenia occurs in a generalized manner, compromising the muscles responsible for stabilization and maintenance of posture, as well as the multifidus, the paravertebral, the deep postural muscles and the transverse ones of the abdomen [13][14][15][16][17] . Thus, an imbalance can occur in the normal biomechanical functioning of the spinal cord, causing dysfunctions and compensations that can trigger pain processes in the area of the lumbar spine [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%